The Influence of Facilities and Service Quality on Visitor Satisfaction in the New Normal: Case Study of Taman Bunga Baturaja - Handayani, Siti Wuria; Gultom, Angga Wibowo (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
This research discussed the influence of Facilities and Service Quality on Visitor Satisfaction (Case Study of Taman Bunga Baturaja in the New Normal). The population of this study was 100 visitors to Taman Bunga Baturaja. The analytical method used was a quantitative method with t count for each variable Facility (X1) of 3,656 and Service Quality (X2) of 2,954 stating that all variables had a significant influence on visitor satisfaction at Baturaja Flower Park. The calculated F value of 14,623 was greater than F table 3.09 which stated that together the facilities and service quality had a significant influence on the satisfaction of visitors to Taman Bunga Baturaja. The value of the coefficient of determination (R Square) of 0.232 means that in this case the contribution of the influence of Facilities and Service Quality on Visitor Satisfaction was 23.2% while the remaining 76.8% was influenced by other variables not mentioned in this case such as as the resulting product, Emotional Factors, Interesting and informative advertisement.